2014
DOI: 10.1002/pc.22999
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of superabsorbent hydrogel and manganese dioxide nanowires composite for adsorption of Pb(II) from aqueous solution

Abstract: The superabsorbent composite was prepared by aqueous solution polymerization, using manganese dioxide, acrylic acid, acrylic amide, 2-acrylamide-2-methyl-1-propanesulfonic acid as raw materials, N,N 0 -methylene bisacrylamide as cross-linker, and K 2 S 2 O 8 as initiator. The composite was characterized by Fourier transform infrared spectrophotometer, thermogravimetric analysis and scanning electron microscopy analysis. This article also described the adsorption behavior of the superabsorbent composite with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, efficient adsorbents become the decisive factor in the adsorption process of heavy metals ions, and the researches on exploring the novel adsorbents with high efficiency for heavy metals adsorption become very essential 4–15 . The development of double network polymer adsorbents for heavy metals adsorption, generally which are prepared by using poly‐blending two kinds of polymer precursor, is highly desirable and is a main challenge in recent years 16–18 . For instance, Zhao et al 19 developed α‐ketoglutaric acid modified chitosan/polyacrylamide semi‐interpenetrating polymer network hydrogen for heavy metals adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, efficient adsorbents become the decisive factor in the adsorption process of heavy metals ions, and the researches on exploring the novel adsorbents with high efficiency for heavy metals adsorption become very essential 4–15 . The development of double network polymer adsorbents for heavy metals adsorption, generally which are prepared by using poly‐blending two kinds of polymer precursor, is highly desirable and is a main challenge in recent years 16–18 . For instance, Zhao et al 19 developed α‐ketoglutaric acid modified chitosan/polyacrylamide semi‐interpenetrating polymer network hydrogen for heavy metals adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15] The development of double network polymer adsorbents for heavy metals adsorption, generally which are prepared by using poly-blending two kinds of polymer precursor, is highly desirable and is a main challenge in recent years. [16][17][18] For instance, Zhao et al 19 developed α-ketoglutaric acid modified chitosan/polyacrylamide semiinterpenetrating polymer network hydrogen for heavy metals adsorption. Azad et al 20 prepared PVB-PVA/Sε-MnO 2 nanocomposite which was used for heavy metals adsorption from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Cametti and co‐workers reported that the complexes formed between cationic liposome and polyelectrolyte complexes (PECs) had the tendency to grow into larger aggregates over time due to thermodynamic instability of the initial complexes. Eishun Tsuchida et al also reported that fibrous structures could form through inter‐complex aggregation following intra‐complex reformation of the initial complexes . Therefore, it's meaningful to investigate the time dependency of both polymeric complexes and the corresponding LbL assembled films.…”
Section: Introductionmentioning
confidence: 99%